PENGARUH RASIO KEUANGAN DAN FAKTOR NON KEUANGAN TERHADAP PENERIMAAN OPINI AUDIT GOING CONCERN - Simanjuntak, Cornellie Tria; Hutasoit, Sri Rejeki Saulina; Simamora, Eva; Hayati, Keumala (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.09.NO.08.TAHUN 2020DO - 10.24843/EEB.2020.v09.i08.p03, 2020)
The contribution of financial ratios in the audit results of financial statements does not fully explain the actual condition of the company so this study adds non-financial factors in explaining the viability of the company (Going Concern). This research analyzes empirical evidence of financial and non-financial factors towards going concern audit opinion. With a population of 141 manufacturing companies listed on the Indonesia Stock Exchange in 2016-2018. The sampling technique method is purposive sampling of 60 samples. The method of data analysis uses logistic regression models. Hypothesis testing results: (1) leverage ratios, (2) client tenure audit, (3) oppinion shopping and (4) KAP reputation have a positive influence or outcome on our research dependent variables 3 Financial factors and 1 Non-financial factors of this study do not give results that affect or negatively affect the dependent variable of our study.